Observation of quantum temporal correlations well beyond Lüders bound - Chun-Wang Wu; Man-Chao Zhang; Yan-Li Zhou; Ting Chen; Ran Huang; Yi Xie; Wen-bo Su; Bao-Quan Ou; Wei Wu; Adam Miranowicz; Franco Nori; Jie Zhang; et al. (Physical Review Research)
The ability of achieving strong quantum spatial correlations has helped the emergence of quantum information science. In contrast, how to achieve strong quantum temporal correlations (QTCs) has remained as a long-standing challenge, thus hindering their applications in time-domain quantum control. Here we experimentally demonstrate that by using a parity-time (PT)–symmetric single ion, the conventional QTC limit known as the Lüders bound can be well surpassed within a standard measurement scenario, approaching the predicted maximum QTC value. Our work, as a step toward quantum engineering of PT devices in the time domain, can stimulate more efforts on operating various quantum devices with the aid of strong QTC resources.